Digital threads in turbulent times: unraveling technostress and cleaner production in the food industry - Irfan, Muhammad; Sulehri, Numair Ahmed; Manickiam, Neelamehan (Frontiers in Robotics and AI, 2024)
In an era underscored by rapid digital transformation and heightened global disruptions, understanding the confluence of digitalization and sustainable business practices is paramount. This study delves deep into the food industries of China and Pakistan, investigating the impact of digitalization on cleaner production. Utilizing a cross-sectional design, we gathered insights from a diverse set of employees through online surveys, with a special focus on the emergent phenomenon of technostress and its subsequent implications. The study's findings reveal a significant influence of digitalization on both resource mobilization and interaction quality. However, technostress emerged as a mediating factor, highlighting the psychological toll of digital transitions. Remarkably, the overarching shadow of the COVID-19 pandemic served as a moderator, altering the dynamics between our study variables. From a theoretical standpoint, our research bridges cleaner production literature with the human-centric nuances of technological adaptation. Practically, it underscores the importance of harmonizing digital strategies with resource mobilization to achieve sustainable outcomes. For the food industry, and potentially beyond, this research offers a roadmap for integrating digital tools into their operations, ensuring both efficiency and cleaner production.